Analysis of the Influence of Product Costs and Promotional Costs on Sales Volume - Suyoto, Rahmat Slamet (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This study discusses the effect of product costs and promotional costs on sales volume (N: 240) using hotel reservation services at PT Intras Tour Yogyakarta. This study aims to determine the effect of product costs and promotional costs on the sales volume of hotel reservations at PT Intras Tour Yogyakarta. The data collection method is the documentation method, in the form of secondary data that has been processed by other parties related to product cost variables in the form of costs to facilitate services and promotional costs in the form of advertising costs and direct marketing costs to the sales volume of hotel reservations. Furthermore, it is processed using Multiple Linear Regression Analysis, F Test, T Test, and the coefficient of Determination. Before processing, the data was tested with the Classical assumptions of the Regression Model, namely the Normality Test, no Multicollinearity, Autocorrelation, and Heteroscedasticity. The results indicate that product costs and promotion costs together or simultaneously have a significant effect on sales volume. Individually or partially product costs have a significant effect on sales volume and promotional costs individually or partially have a significant effect on sales volume. And the element that has more influence on sales is production costs in the form of costs to facilitate service. Keywords: Product Cost, Promotion Cost, Hotel Reservation Sales Volume, PT Intras Tour Garuda.